Fiona Davies - Davies, Fiona (Lawson, N.S.W. : Fiona Davies, 2008)
Website contains images from installations and artworks by Fiona Davies.
Title from title screen (viewed on 9 November 2009)
Text, graphics, sound and video.
Mode of access: Internet via World Wide Web. Available at: http://www.fionadavies.com.au
System requirements: media players for sound and video files.
Selected for archiving
Keywords: Davies, Fiona. -- Exhibitions; Artists -- Australia; Arts, Australian